Virtue and vice in environmental discourse - Dzwonkowska, Dominika (Studia Ecologiae et Bioethicae, 2013)
For effective environmental protection, the necessary tools are not only the external ones in the form of commands, and legal or economic instruments. A very necessary tool for dealing with the environmental crisis can be inner work on one’s own character and personality, as well as on the social virtues and vices that determine our approach to the environment. Recently, a growing interest in environmental virtue discourse can be noticed, and this paper presents a proposal for five cardinal environmental virtues, and oppositional to these, five cardinal vices. The presented virtues are care, moderation, respect, wisdom, and responsibility. On the opposite side of the barricade are the following vices: egoism, greed, arrogance, ignorance (stupidity), and apathy.